Geometrical effects on fuel regression rate in multi-ports design hybrid rocket motor - Ismail, Izham Izzat; Roslan, Mohammad Amirul Qayyum; Azami, Muhammad Hanafi (2024)
The characteristics of a liquid and solid rocket motor are combined in a hybrid rocket motor. It is low-cost, safe, environmentally friendly and throttling-capable. However, the primary reason why hybrid rocket performance is not preferred over other rocket propulsion is its low regression rate. This study is concentrated on lab experiments and analytical calculations related to hybrid rocket motors. A single-port, three-port and four-port shape has been created and built using Solidworks software. The goal of this study is to determine how the number of ports and the oxidizer pressure affect the hybrid rocket motor's regression rate. The performance of the hybrid rocket motor will be represented by this regression rate, which can either increase or decrease. In the lab-scale experiment, the gaseous oxygen is used as the oxidant and paraffin wax as the fuel. The results show that a 200 kPa pressure oxidizer performs better than a 100 kPa, with a difference of 0.0012 m/s at 1 port, 0.0004 m/s at 3 port and 0.0024 m/s at 4 port. The final result demonstrates that four ports at 200 kPa achieved the highest regression rate, which was 0.0073 m/s. On the whole, the results indicate that increasing the number of ports and also oxidizer pressure will improve the regression rate and therefore subsequently increase the performance of the hybrid rocket motor.